DAKWATOLOGI KOMUNIKASI DAN TITIK BIAS KOMUNIKASI - Aep Wahyudin (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
Building a paradigm of Islamic communication does not have to start from scratch. In terms of synthesis base, it can use conventional communication theories. However, it is the taks of Muslim intellectuals and scholars to make a new synthesis through metatheoretical aspects, which includes epistemology, onthology, and perspective. Aspects of values and ethics should be able to collaborate with monotheism and divine responsibility. The function of communication in Islam is to relize the same meaning, leading to changes in the attitudes or behavior of the Muslim community. In the meantime, the ultimate goal of communication in Islam is the happiness in this world and the hereafter, which emphasizes on communication aspects, not communicator. In social change and community development, conventional communication tends to be positivistic and functional and is oriented to individual, not a whole social system. The values of communication such as truth, simplicity, kindness, honesty, integrity, fairness, the validity of message and source, become an important aspect of communciation in Islam. On this perspective, Islam is established on the triangular relationship between God, man, and society.